Clinical Features and Outcomes of Patients with Tetanus at Dr. Hasan Sadikin General Hospital Bandung 2015–2019 - Ananda Pratama Kesumaningtyas Gunawan; Ahmad Rizal Ganiem; Siti Aminah; Lisda Amalia; Sofiati Dian (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Tetanus is a disease characterized by painful muscle spasms all over the body, which still becomes an important health issue worldwide, particularly in developing countries due to the high mortality rate. The clinical features also affect the mortality rate of adult tetanus patients. Tetanus severity score (TSS) is a prognostic scoring system developed in Vietnam that uses clinical features to predict the mortality rate in adult tetanus patients. The aim of this study was to describe the clinical features and outcomes of adult tetanus patients using TSS.Methods: A descriptive, cross-sectional study with a total sampling method was conducted between 2015 and 2019. A total of 71 medical records of adult generalized tetanus patients in the Department of Neurology Dr. Hasan Sadikin General Hospital Bandung were collected to analyze the clinical features and outcomes using TSS. Statistical analysis was performed using SPSS software ver. 25.0.Results: Among seventy-one tetanus patients, 62 (87.3%) were male, and the average age was 55.2±11.2 years. More than half of the patients (71%) were having grade III or worse and experienced dysautonomia complications (57.7%). The mortality rate was 38% and those who survived at discharge, 88.64% had TSS score <8, whereas 37.04% who died had TSS score ≥8.Conclusions: Tetanus in Bandung has a high mortality rate. Those who have died have high TSS scores, while the survivors have low TSS scores, suggesting that the TSS is a prospective scoring to predict the mortality rate in patients with tetanus in Indonesia.